Through their lenses: Arab students' environmental documentation and action. Issue 3 (8th December 2020) - Hayik, Rawia
Abstract: Using the empowering tool of PhotoVoice, this study invites a group of Palestinian-Israeli high-school students to document and report problems in their environment to an invited audience of influential figures from their community. In a context where the focus is on teaching linguistic skills and standards detached from students' lives, students are engaged in literacy activities that are connected with environmental activism. What drives this research is the social responsibility to advance society through fostering environmental awareness and empowering minority students to become more involved and cognizant of their potential to be responsible citizens, leaders, and social change agents, especially with the numerous environmental problems prevalent in their area.